Changes in Intestinal Microbiota Composition in 1-5 Years Old Children with Atopic Dermatitis: Cross Sectional Study - Julia V. Yudina; Alfiia I. Aminova; Andrey P. Prodeus; Anatoly A. Korsunskiy (Union of pediatricians of Russia, 2021)
Background. Atopic dermatitis (AD) arouses high research interest these days due to its significant morbidity rate. The most crucial risk factor for its development is the intestinal microbiota composition. The correlation of this factor with the development of AD in children requires further study.Objective. The aim of the study is to perform comparative analysis of the intestinal microbiota in 1-5 years old children with AD and conditionally healthy children via 16S-sequencing of ribosomal RNA (rRNA) of bacterial genes.Methods. We have conducted cross sectional study. 60 children with diagnosed AD and 15 conditionally healthy children aged from 1 to 5 years were surveyed. Intestinal microbiota was examined via 16S-sequencing of rRNA of bacterial genes.Results. The intestinal microbiota in children with AD and conditionally healthy children has statistically significant differences. Despite the absence of significant differences in species richness of compared groups, children with AD had the elevation in the metagenome of Proteobacteria; Bacilli and Gammaproteobacteria classes; Enterococcaceae and Veillonellaceae families; Eggerthella, Dialister and Enterobacter genus; as well as the decrease in the relative value of Actinobacteria, Bacteroidetes, Verrucomicrobia; Bacteroidales and Bifidobacteriales orders; Bifidobacteriaceae, Bacteroidaceae, Erysipelotrichaceae families; Lachnoclostridium, Roseburia, Prevotella, Coprococcus, Ruminococcus, Faecalibacterium, Bifidobacterium, Bacteroides genus; decrease of Bifidobacterium longum, Faecalibacterium prausnitzii, Bacteroides fragilis.Conclusion. It was revealed that the intestinal microbiota of children with AD has significant differences in taxonomic composition with the microbiota of conditionally healthy children. Elevation of Proteobacteria, Bacilli and Gammaproteobacteria classes, Eggerthella, Dialister and Enterobacter genus can be the risk factor for this disease development, whereas decrease of such bacteria as Verrucomicrobia, Bacteroidales and Bifidobacteriales can aggravate atopic symptoms. Thus, the need for further study of intestinal microbiota in children with AD is justified to establish the correlation of these bacteria with the disease course.